Metal‐Free Dehydrogenation of Amine‐Boranes by Tunable N‐Heterocyclic Iminoboranes. Issue 6 (11th January 2016) - Lui, Melanie W.; Paisley, Nathan R.; McDonald, Robert; Ferguson, Michael J.; Rivard, Eric
Abstract: We report the synthesis of structurally tunable boron complexes supported by N‐heterocyclic imine ligands IPr=N−BR2 (IPr=[(HCNDipp)2 C], Dipp=2, 6‐ i Pr2 C6 H3, R=Cl and/or Ph) that have the ability to abstract dihydrogen from amine‐boranes, and instigate their dehydrocoupling. In one instance, mild heating of the hydrogen addition product IPr=NH−B(Ph)HCl releases H2 to regenerate the starting N‐heterocyclic iminoborane; accordingly IPr=N−B(Ph)Cl can be used as a metal‐free catalyst to promote the dehydrocoupling of MeNH2 ⋅ BH3 to yield N‐methylaminoborane oligomers [MeNH‐BH2 ] x . Abstract : Hydrogen‐stealing : N‐Heterocyclic iminoboranes, IPr=N−BR2 (IPr=[(HCNDipp)2 C], Dipp=2, 6‐ i Pr2 C6 H3, R=Cl and/or Ph) are capable of abstracting dihydrogen from amine‐boranes and instigate their dehydrocoupling. In one instance metal‐free catalytic dehydrocoupling was noted to give oligo( N ‐methylaminoborane)s (see scheme).